Absinthism: a fictitious 19th century syndrome with present impact - Lachenmeier Dirk W; Padosch Stephan A; Kröner Lars U (Substance Abuse Treatment, Prevention, and Policy, 2006)
Abstract Absinthe, a bitter spirit containing wormwood (Artemisia absinthium L.), was banned at the beginning of the 20th century as consequence of its supposed unique adverse effects. After nearly century-long prohibition, absinthe has seen a resurgence after recent de-restriction in many European countries. This review provides information on the history of absinthe and one of its constituent, thujone. Medical and toxicological aspects experienced and discovered before the prohibition of absinthe are discussed in detail, along with their impact on the current situation. The only consistent conclusion that can be drawn from those 19th century studies about absinthism is that wormwood oil but not absinthe is a potent agent to cause seizures. Neither can it be concluded that the beverage itself was epileptogenic nor that the so-called absinthism can exactly be distinguished as a distinct syndrome from chronic alcoholism. The theory of a previous gross overestimation of the thujone content of absinthe may have been verified by a number of independent studies. Based on the current available evidence, thujone concentrations of both pre-ban and modern absinthes may not have been able to cause detrimental health effects other than those encountered in common alcoholism. Today, a questionable tendency of absinthe manufacturers can be ascertained that use the ancient theories of absinthism as a targeted marketing strategy to bring absinthe into the spheres of a legal drug-of-abuse. Misleading advertisements of aphrodisiac or psychotropic effects of absinthe try to re-establish absinthe's former reputation. In distinction from commercially manufactured absinthes with limited thujone content, a health risk to consumers is the uncontrolled trade of potentially unsafe herbal products such as absinthe essences that are readily available over the internet.